The comparison of the unit cost of hemodialysis with ina cbg rates in Muhammadiyah Siti Aminah Hospital - gigin bian rosmila; Rizal Yaya; Firman Pribadi (Archives of Business Research, 2020)
Health services in Indonesia have led to the National Health Insurance. Hospitals that serve BPJS participants are paid using a package system based on INA CBG rates. Payment of claims to advanced health facilities is differentiated by type of hospital. Type D hospitals have the lowest INA CBG rates, so they must calculate the unit cost of each procedure given based on the diagnostic group. The purpose of this study was to determine the comparison of the unit cost of hemodialysis measures with INA CBG rates and to find out if there are non-value-added activities in services. This type of research was a qualitative case study. The subject of the study was Muhammadiyah Siti Aminah General Hospital. The object used was all activities that support the occurrence of hemodialysis outpatient services. Data analysis used Activity Based Costing Baker modification. The results shows a unit cost of HD action in 2018 of Rp. 724.725. INA CBG rate for hemodialysis action in Type D Hospital is Rp. 737.700,-. So that a positive difference is obtained between the INA CBG rate and the HD unit cost of Rp. 12,975 -. RSUMSA has not been able to conduct supporting examinations in accordance with the specified standards because the costs incurred will be very high and will cause losses because they exceed INA CBGS tariffs and no potential non-value added activities are found. Keywords: Unit Cost; Hemodialisis; Tarif INA CBG